Pengukuran dan Evaluasi Potensi Bahaya Ergonomi di Tempat Kerja - Ardiansyah, Muhammad Adam; Ramdhan, Doni Hikmat (Jurnal EMT KITA, 2024)
This research aims to identify and evaluate ergonomic risks associated with pipe lifting activities using rod loaders in the PT 5/2018 concerning K3 Work Environment, measuring and controlling ergonomic risk factors is important to ensure safe K3 Work Environment conditions. The ergonomic measurement method used refers to the Indonesian National Standard (SNI) 9011:2021. This research uses a comparative approach with data collection techniques through field observations, data-based questionnaires, and GOTRAK complaint surveys. The research results show that pipe lifting activities with rod loaders have significant ergonomic risks, especially related to manual material handling. More than 30% of Drill Helper workers experienced GOTRAK complaints classified as moderate-severe. Recommended measures include workplace ergonomics assessments, ergonomic workplace redesign, training on ergonomics, and use of appropriate equipment to reduce the risk of injury and musculoskeletal disorders in workers.